Risk Factor Of Substitution ARV First Line People Living With HIV/AIDS In General Hospital Buleleng Bali - Luh Putu Desy Puspaningrat; Gusti Putu Candra; Putu Dian Prima Kusuma Dewi; I Made Sundayana; Indrie Lutfiana (Universitas STRADA Indonesia, 2020)
Substitution is still a threat to the failure of ARV therapy so that no matter how small it must be noted and monitored in ARV therapy. The aims was analysis risk factor substitution ARV first line in therapy ARV. This study was an analytic longitudinal study with retrospective secondary data analysis in a cohort of patients receiving ARV therapy at the District General Hospital of Buleleng District for the period of 2006-2015 and secondary data from medical records of PLHA patients receiving ART. Result in this study that the percentage of first-line ARV substitution events is 9.88% (119/1204) who received ARV therapy for the past 11 years. Risk factors that increase the risk of substitution in ARV therapy patients are zidovudine (aOR 4.29 CI 1.31 -2.65 p 0.01), nevirapine (aOR1.86 CI 2.15 - 8.59 p 0.01) and functional working status (aOR 1.46 CI 1.13 - 1.98 p 0.01).